2012
DOI: 10.3109/10731199.2012.716067
|View full text |Cite
|
Sign up to set email alerts
|

Swine hemoglobin as a potential source of artificial oxygen carriers, hemoglobin-vesicles

Abstract: Hemoglobin-based oxygen carriers (HBOCs) have been developed as a transfusion alternative and oxygen therapy. The Hb source is usually outdated donated human blood or cow blood obtained from cattle industries because of its abundance. This study examined the feasibility of using swine Hb ((S)Hb) for preparation of cellular-type HBOCs, hemoglobin-vesicles (HbV). Purification of (S)Hb from fresh swine whole blood was conducted with processes including carbonylation ((S)HbO(2) --> (S)HbCO), pasteurization (60 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The absence of hemichrome formation in the experiments by Mudhivarthi et al may be attributed to the fact that HbA has a much larger heme pocket than LtEc, thereby decreasing the likelihood of contact between the heme and distal histidine [11]. In conclusion, while it has been previously shown that human hemoglobin-based oxygen carriers can be sterilized via pasteurization in the presence of CO [22], our results suggest that it is not possible to sterilize native LtEc or LPE particles with pasteurization or autoclaving. Therefore, additional experiments will need to be conducted to develop a sterilization method that inactivates viruses while maintaining the O 2 transport properties of LtEc and/or LPE.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of hemichrome formation in the experiments by Mudhivarthi et al may be attributed to the fact that HbA has a much larger heme pocket than LtEc, thereby decreasing the likelihood of contact between the heme and distal histidine [11]. In conclusion, while it has been previously shown that human hemoglobin-based oxygen carriers can be sterilized via pasteurization in the presence of CO [22], our results suggest that it is not possible to sterilize native LtEc or LPE particles with pasteurization or autoclaving. Therefore, additional experiments will need to be conducted to develop a sterilization method that inactivates viruses while maintaining the O 2 transport properties of LtEc and/or LPE.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last years artificial blood substitutes have gained more and more attention because of the above mentioned decrease of available RBCs (Ruchalla 2013, Njoku et al 2015, Chung et al 2016, Ellingson et al 2017, Taguchi et al 2017, Ferenz and Steinbicker 2019. Since the application of a pure solution of haemoglobin is impractical due to the enormous nephrotoxicity and short circulation time (Chang 2006), several different attempts have been made to create biocompatible artificial oxygen carriers, based on either perfluorocarbons or haemoglobin that needs to be encapsulated in protective shells in any case (Bauer et al 2010, von Storp et al 2012, Ferenz et al 2013, Sakai et al 2013, Stephan et al 2014, Wrobeln, Laudien, et al 2017, Wrobeln, Schlüter, et al 2017.…”
Section: Introductionmentioning
confidence: 99%